Curriculum 4.0: Adoption of Industry Era 4.0 as Assessment of Higher Education Quality - Chandra Lukita; Suwandi Suwandi; Eka Purnama Harahap; Untung Rahardja; Chairun Nas (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2020)
Indonesia is the 4th largest country in Southeast Asia with a population of 262 million which needs to be considered the success rate of its human resources, because of a strong country that has a strong foundation, one example is the intelligence of human resources. Global competition proves that HR requires strong competence in all fields, generally in the field of technology. However, the lack of equitable education, as well as the conventional education system, makes the country of Indonesia far behind compared to other neighboring countries. The challenge of this 4.0 era is an opportunity to bring up the development of a combination of Industry 4.0 and the education curriculum in Indonesia. There are four issues why the Indonesian education system and curriculum needs to be reviewed. Where there is a literature study and SWOT analysis method used as a reference in solving problems and there is a significant scope. In this paper, competencies are needed to enable success between the integration of education management and the industrial era 4.0 which will be discussed and analyzed based on the facts and reality of the education system in Indonesia which can then be presented in a comprehensive curriculum.